Institutions, Norms, and Self-Belief: A Moderated-Mediated Model of Women’s Political Participation - Shahab, Muhammad; Sultana, Razia; Sultana, Baserat; Rajan, Shanthi; Amin, Lubna; Naseem, Imran; Ozturk, Ilknur; Zaman, Khalid (International Review of Management and Marketing, 2026)
In South Asia, institutional, socio-cultural, and economic barriers prevent women from participating in politics, a prerequisite for democracy. This study examines how educational attainment, economic independence, community and family support, and political party membership affect women’s political involvement in Sri Lanka, Pakistan, and India. The study also evaluates the moderating effects of cultural norms and the mediating effects of political self-efficacy using a single analytical approach. A quantitative cross-sectional survey obtained primary data from 1,035 women in all three countries. These women had diverse careers and social backgrounds. The data were evaluated using Structural Equation Modeling to determine direct, mediated, and moderated relationships among constructs. The study shows that educational performance, economic independence, family/community support, and political party inclusion influence women’s political involvement. Psychological empowerment converts resources into involvement, and political self-efficacy partially regulates social and institutional support. Limited cultural norms reduce the influence of economic independence and education on political engagement. Combining economic, structural, and psychological factors creates an integrated overview of South Asian women’s political involvement. The findings affect policymakers and political organizations seeking to remove cultural and institutional impediments to female empowerment and inclusive governance.